2016
DOI: 10.1038/srep36321
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gamma oscillations in the inferior occipital gyrus in response to eyes

Abstract: Eyes are an indispensable communication medium for human social interactions. Although previous neuroscientific evidence suggests the activation of the inferior occipital gyrus (IOG) during eye processing, the temporal profile of this activation remains unclear. To investigate this issue, we analyzed intracranial electroencephalograms of the IOG during the presentation of eyes and mosaics, in either averted or straight directions. Time–frequency statistical parametric mapping analyses revealed greater gamma-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Cognitive assessment in patients with epilepsy requires a multifactorial and neurodevelopmental model because the oculomotor nerve test evaluates response inhibition and working memory through related tasks [ 39 ]. Some researchers believe that eye movement is a marker of CI in people with epilepsy [ 48 ]. Amador et al study thinks ET tasks are associated with each other and the severity of the disease, suggesting that eye movement may be a useful tool in studying advanced cognitive functions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive assessment in patients with epilepsy requires a multifactorial and neurodevelopmental model because the oculomotor nerve test evaluates response inhibition and working memory through related tasks [ 39 ]. Some researchers believe that eye movement is a marker of CI in people with epilepsy [ 48 ]. Amador et al study thinks ET tasks are associated with each other and the severity of the disease, suggesting that eye movement may be a useful tool in studying advanced cognitive functions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of IXT was also found to be positively correlated with FC between the IOG and right V1, which indicated that as the disease progresses, the FC between the V1 and IOG becomes stronger. The IOG participates in the initial stages of visual processing ( 50 ). Previous studies have shown that through extensive practice of challenging visual tasks, brain plasticity can be induced in adults with amblyopia ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…IOG is the most posterior brain region and one of core human neural systems for face perception, which is associated with initial stage of face processing, speci cally, the processing of facial features (40). And gamma oscillations of right IOG are related to the early stages of eye processing (41). The inferior occipital gyrus has been implicated as an important region for emotion regulation in mood disorders (42).…”
Section: Discussionmentioning
confidence: 99%